2020
DOI: 10.1021/acsami.0c00412
|View full text |Cite
|
Sign up to set email alerts
|

Modulated Sn Oxidation States over a Cu2O-Derived Substrate for Selective Electrochemical CO2 Reduction

Abstract: Pursuing high catalytic selectivity is challenging but paramount for an efficient and low-cost CO2 electrochemical reduction (CO2R). In this work, we demonstrate a significant correlation between the selectivity of CO2R to formate and the duration of tin (Sn) electrodeposition over a cuprous oxide (Cu2O)-derived substrate. A Sn electrodeposition time of 120 s led to a cathode with a formate Faradaic efficiency of around 81% at −1.1 V vs reversible hydrogen electrode (RHE), which was more than 37% higher than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 42 publications
0
39
0
Order By: Relevance
“…Previous studies have shown that Cu–Sn alloys can realize both CO 2 -to-CO 27 , 28 and CO 2 -to-formate reaction pathways 29 , 30 (see Supplementary Table 2 ). Although insights have been gained in terms of morphology 31 , structure 30 , valence state 32 , and composition 29 , the mechanistic understanding of Cu–Sn alloys at the isolated atomic interfaces and the root behind different CO 2 RR pathways remain elusive. In this study, the three-dimensional atomic structure of the Cu–Sn surface alloy is established by using the atom probe tomography (APT) and high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that Cu–Sn alloys can realize both CO 2 -to-CO 27 , 28 and CO 2 -to-formate reaction pathways 29 , 30 (see Supplementary Table 2 ). Although insights have been gained in terms of morphology 31 , structure 30 , valence state 32 , and composition 29 , the mechanistic understanding of Cu–Sn alloys at the isolated atomic interfaces and the root behind different CO 2 RR pathways remain elusive. In this study, the three-dimensional atomic structure of the Cu–Sn surface alloy is established by using the atom probe tomography (APT) and high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM).…”
Section: Introductionmentioning
confidence: 99%
“…However, achieving high product selectivity at industrially relevant current densities remains a crucial challenge in the large‐scale deployment of CO 2 R technologies [2] . Advances in new electrocatalyst materials for CO 2 R [3–12] provide a crucial strategy to improve the selectivity and activity. Still, there is a need to better understand how CO 2 and electrolytes interact with the catalysts and how these interactions during CO 2 R can play a significant role in enhancing CO 2 R selectivity and activity [13–16] .…”
Section: Introductionmentioning
confidence: 99%
“…Gas chromatograph (GC‐7820, Zhongkehuifen, China) equipped with both thermal conductivity detector (TCD) and flame ionization detector (FID) was used to quantify the gas‐phase products. The FE i of gas product species‐CO and H 2 was calculated by [34] trueFEi=(ni×F×P×v×ci)/(R×T×j)×1000.166667em% …”
Section: Methodsmentioning
confidence: 99%